Числовое управление. Основы САМ учебное пособие - Сикора, Е. А. специалист в области машиностроения доцент кафедры автоматизации и роботизации в машиностроении Томского политехнического университета 1984- (Изд-во ТПУ, 2012)
The textbook is intended for studying basics of conventional numerical control, numerical control part programming and computer controls, choice of means, development cycles to create specialized databases. Some features of the most widespread methods and devices in the field are also considered and discussed. The study aid has been designed in the framework of the Bachelor Degree Program Design and Technological Support of Mechanical Engineering jvianutactures (150900) at the Automation and Robotics Department of Tomsk Polytechnic University.